Analisis Semiotika Kehidupan Jurnalis dalam Drama Korea HUSH - Ellyda Retpitasari; Nurul Fadilah; Risky Maulana (Journal of Islamic Communication Studies, 2024)
This journal is an analysis of semiotics that focuses on the life of an idealistic senior journalist in the Korean drama HUSH. Through a semiotic approach, this journal reveals how the signs and symbols in the drama influence the main character and play a significant role in the plot's development. Semiotic analysis Roland Barthes is used to understand the meaning conveyed by the signs that appear in this drama. The journal author investigates how visual signs, such as facial expressions, body language, and the characters' attire, are employed to depict emotions, personalities, and character transformations. Furthermore, the author examines the use of symbols in the background, objects, and scene setups, which add a narrative dimension to the story. In this journal, the main focus is on the central character, Lee Ji-soo, a senior journalist with a strong sense of idealism. The author explains how the signs surrounding Ji-soo, such as the events she experiences and interactions with other characters, influence her transformation into a more experienced and mature journalist. Additionally, the journal highlights the role of internal conflicts faced by Ji-soo in carrying out her profession. The author discusses how the signs and symbols that emerge in the drama reflect the moral and ethical dilemmas Ji-soo encounters in reporting news and their impact on her integrity as an idealistic journalist. Drama Hush provides a strong depiction of journalistic ethics and provides an understanding of the complexity of the world of journalism in South Korea, in the perspective of the Qur'an and Hadith in viewing the film Hush emphasizes journalistic ethics, especially honesty in accordance with the Qur'an al-Ahzab verse 70 Prophetic Hadith narrated by Abdullah Bin Mas'ud from Hadith History Muslim.